2023
DOI: 10.3390/en17010159
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing LOCA Breach Size Diagnosis with Fundamental Deep Learning Models and Optimized Dataset Construction

Xingyu Xiao,
Ben Qi,
Jingang Liang
et al.

Abstract: In nuclear power plants, the loss-of-coolant accident (LOCA) stands out as the most prevalent and consequential incident. Accurate breach size diagnosis is crucial for the mitigation of LOCAs, and identifying the cause of an accident can prevent catastrophic consequences. Traditional methods mostly focus on combining model algorithms and utilize intricate composite model neural network architectures. However, it is crucial to investigate whether greater complexity necessarily leads to better performance. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, the study of the Fukushima accident has shown that the agreement of simulation results with NCEP data is better than that with ECMWF data [147]. The detection data prepare the groundwork for subsequent aging monitoring systems [148], situation awareness [149], and fault diagnosis [150].…”
Section: Monitoring and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study of the Fukushima accident has shown that the agreement of simulation results with NCEP data is better than that with ECMWF data [147]. The detection data prepare the groundwork for subsequent aging monitoring systems [148], situation awareness [149], and fault diagnosis [150].…”
Section: Monitoring and Detectionmentioning
confidence: 99%
“…Data-driven methods for fault diagnosis in NPPs have attracted increasing interest in recent years. They include artificial neural networks (ANNs) [150,153,154], support vector machines (SVMs), decision trees (DTs), principal component analysis (PCA), and clustering [155]. Certainly, numerous studies have also opted for hybrid algorithms [155].…”
Section: Fault Diagnosismentioning
confidence: 99%